The Transformative Potential of Between-Stage Space for White Teacher Practice at a Mostly-White High School - Stahl, Sooz (My University, 2020)
The culture and climate of schools dominated by White, privileged students present distinct challenges for educators who wish to equitably serve all students, especially those who have been marginalized due to their social identities. In order for students who attend predominantly White schools to be educated for meaningful participation in a global society, teachers at such schools must adopt a critical pedagogical stance to (a) understand how racism affects marginalized students and (b) disrupt behaviors that uphold White supremacy and other forms of oppression in the school setting. These concerns were the guiding force for this study of the types of transformation that occurred in my practice after teaching a course in Augusto Boal’s (2008) Theatre of the Oppressed techniques at a predominantly White high school. Data from this self-study were collected, analyzed, and presented using a blend of portraiture methodologies that included scripts based on Augusto Boal’s (2002) Forum Theatre model. The presentation of the findings in this way is intended to inspire transformative action from the reality of White Savior teacher practice toward a more liberatory ideal (Boal, 2002), though it must be acknowledged from the outset that White teachers are not in a position to liberate students of color (more on this later). Data generated by this study demonstrated that a White female teacher in a predominantly White school setting can enact what I call White Savior teacher practice even as she strives to reduce harm caused by racism and other forms of oppression. Findings also show that harm-reduction pedagogy can emerge from practicing Theatre of the Oppressed with youth in mostly-White schools. Data were collected from self-generated documents, student journal writing and drawing, video recordings of course sessions, and semi-structured interviews. The study took place in an urban school district in the Pacific Northwest. The setting of the study was a large predominantly White high school in a prosperous area where White families have historically resorted to litigation to push back against district efforts to integrate its schools. Participants ranged in age from 15 to 18 years old. Half of the participants were White and half were students of color; six were Latinx (from Mexico, the Dominican Republic, and Honduras), two were biracial (White and African American), and one was a Pacific Islander whose family hails from Tonga. I constructed a framework that defines four different types of White teacher practice, with axes delineating a teacher’s motivations and attitudes toward the status quo, which I employed to analyze data about my own practice. Data analysis revealed evidence of the White savior paradigm in my teaching, including “White Washed” assimilationist ideology in expectations of academic conduct and participation; White voices (including my own) dominating discourse in the front stage space of classroom instruction and discussions; failure to empower the most marginalized students and engage them in creating their own vision of success and emancipation. Data analysis also revealed some transformations in the ways I teach and my orientation toward mostly-White educational contexts. During the project, I validated the perspectives of students of color by centering them in course content and professional presentations, positioning them as experts and creating opportunities for student-centered dialogue. I taught about institutional and systemic oppression and explained how personal words and actions can be hurtful even though unintentional. I disrupted oppressive institutional forces of academia and traditional notions of “doing school” by designing collaborative and unifying student experiences. Data collected after the project with students ended showed that I have learned to name my own positionality as a White person and to explain the privilege that it entails. In my current practice I model this transparency for White students and explicitly encourage White students to monitor their language and behavior in classroom-based interactions. I am exploring the value and limitations of creating backstage space for White students to process their emerging understanding of White privilege and White supremacy (in caucusing spaces, for example) without burdening students of color. With colleagues and administrators, I am now more skilled and assertive in critiquing the status quo in both front stage and backstage space, specifically drawing attention to colorblindness, deficit thinking, and assumptions rooted in White supremacy. Despite these findings, I acknowledge that White supremacy is the metaphorical water in which I have been socialized, and thus will always be a lurking influence in my teaching practice. I am committed to being vigilant in recognizing the ways it shows up and engaging in critical reflection toward continued growth and progress. Findings suggest that TO can facilitate fruitful critical examination of boundary-crossing, mask-wearing, transparency, vulnerability, and trust that can lead to positive transformation in White teacher practice in predominantly White schools. Following the presentation and analysis of my findings, recommendations are presented for future research to further understanding of ways that Theatre of the Oppressed can be practiced with youth in such settings.
Thesis (Ph.D.)--University of Washington, 2019
Keywords: Goffman; Metaxis; Theatre of the Oppressed; Transformation; White Savior; White Teacher; Multicultural education; Theater; Education - Seattle